Energy Drinks May Affect the Ovarium (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Energy drinks have an impact on concentration levels, physical performance, speed of reaction, and focus, but these drinks cause many adverse effects and intoxication symptoms. The main goal of this study was to determine the effect of energy drink consumption on ovarian reserve and serum anti-mullerian hormone (AMH) levels.Female Wistar albino rats (n=16) were included and randomized into two groups (n=8). Serum AMH levels were checked before and after energy drinks were given. Eight weeks later, the ovaries and uteruses of the rats were analyzed histopathologically. The number of follicles in the ovaries was counted.The total number of the preantral plus small antral follicles, which show the ovarian reserve, was decreased at the end of eight weeks in both the control group and the energy drink group.